2001
DOI: 10.1152/ajpgi.2001.280.5.g910
|View full text |Cite
|
Sign up to set email alerts
|

HGF regulates tight junctions in new nontumorigenic gastric epithelial cell line

Abstract: The regulation of intercellular adhesion by hepatocyte growth factor (HGF) was examined on a novel nontumorigenic gastric epithelial cell line (IMGE-5) derived from H-2Kb-tsA58 transgenic mice. IMGE-5 cells constitutively expressed cytokeratin 18 and HGF receptors. Under permissive conditions (33 degrees C + interferon-gamma), IMGE-5 cells proliferated rapidly but did not display membrane expression of adherens and tight junction proteins. Under nonpermissive conditions, their proliferation was decreased and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 40 publications
4
65
1
Order By: Relevance
“…Further studies are needed to find the experimental conditions under which the cells produce mucin. Recently, Hollande et al (2001) reported establishing a gastric epithelial cell line, IMGE-5, which displays membrane expression of adhesion and tight junction proteins from the tsSV40 large T-antigen TG mice. However, the cells did not express specific markers for pit, parietal, or zymogenic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are needed to find the experimental conditions under which the cells produce mucin. Recently, Hollande et al (2001) reported establishing a gastric epithelial cell line, IMGE-5, which displays membrane expression of adhesion and tight junction proteins from the tsSV40 large T-antigen TG mice. However, the cells did not express specific markers for pit, parietal, or zymogenic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, various cell lines with specific functions from different organs have been established by using TG mice, e.g., hepatocytes (Yanai et al, 1991), colonic epithelial cells (Tabuchi et al, 2000), testicular Leydig and Sertoli cells . Furthermore, we and others have succeeded in establishing pit (gastric surface mucous) cell lines, GSM06 and GSM10 (Sugiyama et al, 1993;Tabuchi, 2001), and a gastric epithelial cell line, IMGE-5, from the TG mice (Hollande et al, 2001). More recently, TG rat harboring the tsSV40 large Tantigen gene was also developed as a source of conditionally immortalized cell lines (Takahashi et al, 1999).…”
mentioning
confidence: 99%
“…HGF is known to decrease TER in many cell lines (51,52); and unlike EGF, HGF induces epithelial-mesenchymal transitions in MDCK II cells grown on plastic (53). Quiescent and polarized MDCK cells were treated with 20 ng/ml HGF, a concentration known to induce cell scattering in MDCK cells (54); and changes in claudin expression were determined.…”
Section: Pattern Of Hepatic Growth Factor (Hgf)-induced Alterations Imentioning
confidence: 99%
“…[26][27][28] The dynamic nature of tight junctions is well demonstrated by the ability of cytokines and growth factors to modulate tight junction protein expression, regulate junction assembly and change epithelial permeability. [29][30][31][32][33] It has been established for many years that the cytokine profile of CD is T-helper type 1 and shows increased expression of the cytokines, TNFa and IFNg. 34,35 The situation in ulcerative colitis (UC) is less clear.…”
mentioning
confidence: 99%